A SQUID system for geophysical measurements cooled by a pulse tube cryocooler. (8th June 2018) - Schmidt, Bernd; Falter, Jens; Schirmeisen, André; Mück, Michael
Abstract: Geophysical measurements, which rely on the acquisition of magnetic data, can take advantage of a superconducting quantum interference device (SQUID), which offers a higher field sensitivity at lower frequencies than conventional induction coils. Although cooling a SQUID in liquid helium provides for a simple and low-interference system, in remote areas a cryocooler could reduce the expenses of operation. We studied transient magnetic measurements with a SQUID cooled by a small pulse tube cooler operated by a 1 kW compressor, which can be powered by a portable generator or large truck battery.